A case of tuberculosis verrucosa cutis in Brazil undiagnosed for 15 years - Wedy, Glaucia Ferreira; Passero, Luiz Felipe Domingues [UNESP]; Criado, Paulo Ricardo; Belda, Walter (Elsevier, 2021)
Tuberculosis verrucosa cutis is a rare medical condition that is caused by the inoculation of Mycobacterium tuberculosis into the skin of a previously sensitized individual. This clinical form of tuberculosis corresponds to 1–2% of all cases of tuberculosis and due to the paucibacillary characteristic of the lesions, patients can be misdiagnosed, accounting for the chronification of the skin infection. Herein, we report the case of a 26-year-old male farmer, presenting plaques with verrucosa and hyperkeratosis features in the left thigh and buttocks during 15 years. M. tuberculosis was identified by PCR and the patient was treated with standard anti-tuberculosis drugs, with subsequent improvement of the skin lesions.
Keywords: Mycobacterium tuberculosis; Skin; Treatment; Tuberculosis verrucose cutis